A combined gas-phase dissociative ionization, dissociative electron attachment and deposition study on the potential FEBID precursor [Au(CH3)2Cl]2 - Bilgilisoy, Elif; Kamali, Ali; Gentner, Thomas; Ballmann, Gerd; Harder, Sjoerd; Steinrück, Hans-Peter; Marbach, Hubertus; Ingólfsson, Oddur (Beilstein Journal of Nanotechnology, 2023)
Motivated by the potential of focused-electron-beam-induced deposition (FEBID) in the fabrication of functional gold nanostructures for application in plasmonic and detector technology, we conducted a comprehensive study on [Au(CH3)2Cl]2 as a potential precursor for such depositions. Fundamental electron-induced dissociation processes were studied under single collision conditions, and the composition and morphology of FEBID deposits fabricated in an ultrahigh-vacuum (UHV) chamber were explored on different surfaces and at varied beam currents. In the gas phase, dissociative ionization was found to lead to significant carbon loss from this precursor, and about 50% of the chlorine was on average removed per dissociative ionization incident. On the other hand, in dissociative electron attachment, no chlorine was removed from the parent molecule. Contrary to these observations, FEBID in the UHV setup was found to yield a quantitative loss and desorption of the chlorine from the deposits, an effect that we attribute to electron-induced secondary and tertiary reactions in the deposition process. We find this precursor to be stable at ambient conditions and to have sufficient vapor pressure to be suitable for use in HV instruments. More importantly, in the UHV setup, FEBID with [Au(CH3)2Cl]2 yielded deposits with high gold content, ranging from 45 to 61 atom % depending on the beam current and on the cleanliness of the substrates surface.
CRIS-Team Scopus Importer:2024-12-16
Keywords: dissociative electron attachment; dissociative ionization; focused-electron-beam-induced deposition (FEBID); gold deposit; low-energy electrons; quantum chemical calculation; ultrahigh vacuum

Dinitrogen complexation and reduction at low-valent calcium - Rösch, Bastian; Gentner, Thomas; Langer, Jens; Färber, Christian; Eyselein, Jonathan; Zhao, L.; Ding, C.; Frenking, G.; Harder, Sjoerd (Science, 2021)
Here we report that attempted preparation of low-valent CaI complexes in the form of LCa-CaL (where L is a bulky b-diketiminate ligand) under dinitrogen (N2) atmosphere led to isolation of LCa(N2)CaL, which was characterized crystallographically. The N22- anion in this complex reacted in most cases as a very potent two-electron donor. Therefore, LCa(N2)CaL acts as a synthon for the low-valent CaI complex LCa-CaL, which was the target of our studies. The N22- anion could also be protonated to diazene (N2H2) that disproportionated to hydrazine and N2. The role of Ca d orbitals for N2 activation is discussed.
CRIS-Team Scopus Importer:2021-03-26

Heteroleptic Heavier Alkaline Earth Metal Amide Complexes Stabilized by a Superbulky β-Diketiminate Ligand - Gentner, Thomas; Rösch, Bastian; Thum, Katharina; Langer, Jens; Ballmann, Gerd; Pahl, Jürgen; Donaubauer, Wolfgang; Hampel, Frank; Harder, Sjoerd (Organometallics, 2019)
Heteroleptic alkaline earth metal (Ae = Ca, Sr, Ba) amide complexes with the superbulky β-diketiminate ligand DIPePBDI (CH[C(Me)N-DIPeP]2, DIPeP = 2,6-di-iso-pentylphenyl) have been prepared by direct deprotonation of DIPePBDI-H with either AeN′′2 or AeN′′2·(THF)2 (N′′ = N(SiMe3)2). Despite long reaction times of 5-14 days, this convenient one-step synthetic method has the major advantage that metal-pure products are obtained in generally quantitative yields. All (DIPePBDI)AeN′′ and (DIPePBDI)AeN′′·THF complexes are monomeric and stabilized by agostic metal···Me3Si and metal···iso-pentyl interactions. They are highly soluble in toluene and indefinitely stable toward ligand scrambling, even after 2 weeks at 140 °C. The same series with the smaller DIPPBDI ligand (CH[C(Me)N-DIPP]2, DIPP = 2,6-di-iso-propylphenyl) could, except for Ca, also be prepared by direct ligand deprotonation. The (DIPPBDI)CaN′′ and (DIPPBDI)CaN′′·THF complexes are stable toward ligand exchange up to 110 °C. Whereas THF-free (DIPPBDI)SrN′′ and (DIPPBDI)BaN′′ decompose at 50 and 20 °C, respectively, their THF adducts were found to be stable up to 60 °C. This is, however, strongly dependent on complex purity. Slight hydrolysis or contamination with KN′′ accelerates ligand scrambling. Therefore, partial hydrolysis and salt metathesis routes that involve KN′′ should be avoided when synthesizing heteroleptic complexes of the heavier Ae metals.
CRIS-Team Scopus Importer:2019-07-09

Low Valent Magnesium Chemistry with a Super Bulky β-Diketiminate Ligand - Gentner, Thomas; Rösch, Bastian; Ballmann, Gerd; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
The steric bulk of the well-known DIPP BDI ligand (CH[C(CH 3 )N-DIPP] 2 , DIPP=2,6-diisopropylphenyl) was increased by replacing isopropyl for isopentyl groups. This very bulky DIPeP BDI ligand could not stabilize the radical species ( DIPeP BDI)Mg . : reduction of ( DIPeP BDI)MgI with Na gave ( DIPeP BDI) 2 Mg 2 with a rather long Mg-Mg bond of 3.0513(8) Å. Addition of TMEDA prior to reduction gave complex ( DIPeP BDI) 2 Mg 2 (C 6 H 6 ), which could also be obtained as its THF adduct. It is speculated that combination of a bulky spectator ligand and TMEDA prevents dimerization of the intermediate Mg I radical, which then reacts with the benzene solvent. Complex ( DIPeP BDI) 2 Mg 2 (C 6 H 6 ), which formally contains the anti-aromatic anion C 6 H 6 2− , reacted with tBuOH as a Brønsted base to 1,3- and 1,4-cyclohexadiene and with H 2 as a two electron donor to ( DIPeP BDI) 2 Mg 2 H 2 and C 6 H 6 . It also reductively cleaved the C−F bond in fluorobenzene and gave ( DIPeP BDI)MgPh, ( DIPeP BDI)MgF, and C 6 H 6 .
CRIS-Team Scopus Importer:2019-08-16
Keywords: alkaline earth metal; bulky ligand; low valence; magnesium; metal-metal bonding

Mg-Mg bond polarization induced by a superbulky β-diketiminate ligand - Rösch, Bastian; Gentner, Thomas; Eyselein, Jonathan; Friedrich, Alexander; Langer, Jens; Harder, Sjoerd (Chemical Communications, 2020)
The bulk of a recently reported superbulky β-diketiminate ligand was further increased by introducing tBu substituents in the ligand backbone. Attempts to isolate free Mg radicals with this extremely bulky ligand failed. Instead, a dinuclear Mg(i) complex with one chelating and one monodentate β-diketiminate ligand was isolated. Asymmetry in metal coordination results in a polarized Mg-Mg bond.
CRIS-Team Scopus Importer:2020-10-09

Nucleophilic Aromatic Substitution at Benzene with Powerful Strontium Hydride and Alkyl Complexes - Rösch, Bastian; Gentner, Thomas; Elsen, Holger; Fischer, Christian; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
Key to the isolation of the first alkyl strontium complex was the synthesis of a strontium hydride complex that is stable towards ligand exchange reactions. This goal was achieved by using the super bulky beta-diketiminate ligand (BDI)-B-DIPeP (CH[C(Me)N-DIPeP](2), DIPeP = 2,6-diisopentylphenyl). Reaction of (BDI)-B-DIPeP-H with Sr[N(SiMe3)(2)](2) gave ((BDI)-B-DIPeP)SrN(SiMe3)(3) which was converted with PhSiH3 into [((BDI)-B-DIPeP)SrH2]. Dissolved in C6D6, the strontium hydride complex is stable up to 70 degrees C At 60 degrees C, H-D isotope exchange gave full conversion into ([(BDI)-B-DIPeP)SrD](2) and C6D5H. Since H-D exchange with D-2 is facile, the strontium hydride complex served as a catalyst for the deuteration of C6H6 by D-2. Reaction of [( (BDI)-B-DIPeP)SrH](2) with ethylene gave [( (BDI)-B-DIPeP)SrEt](2). The high reactivity of this alkyl strontium complex is demonstrated by facile ethylene polymerization and nucleophilic aromatic substitution with C6D6, giving alkylated aromatic products and [((BDI)-B-DIPeP)SrD](2).
CRIS-Team WoS Importer:2019-04-23

On the Electron-Induced Reactions of (CH3)AuP(CH3)(3): A Combined UHV Surface Science and Gas-Phase Study - Kamali, Ali; Bilgilisoy, Elif; Wolfram, Alexander; Gentner, Thomas; Ballmann, Gerd; Harder, Sjoerd; Marbach, Hubertus; Ingolfsson, Oddur (Nanomaterials, 2022)
Focused-electron-beam-induced deposition (FEBID) is a powerful nanopatterning technique where electrons trigger the local dissociation of precursor molecules, leaving a deposit of non-volatile dissociation products. The fabrication of high-purity gold deposits via FEBID has significant potential to expand the scope of this method. For this, gold precursors that are stable under ambient conditions but fragment selectively under electron exposure are essential. Here, we investigated the potential gold precursor (CH3)AuP(CH3)(3) using FEBID under ultra-high vacuum (UHV) and spectroscopic characterization of the corresponding metal-containing deposits. For a detailed insight into electron-induced fragmentation, the deposit's composition was compared with the fragmentation pathways of this compound through dissociative ionization (DI) under single-collision conditions using quantum chemical calculations to aid the interpretation of these data. Further comparison was made with a previous high-vacuum (HV) FEBID study of this precursor. The average loss of about 2 carbon and 0.8 phosphor per incident was found in DI, which agreed well with the carbon content of the UHV FEBID deposits. However, the UHV deposits were found to be as good as free of phosphor, indicating that the trimethyl phosphate is a good leaving group. Differently, the HV FEBID experiments showed significant phosphor content in the deposits.
CRIS-Team WoS Importer:2022-08-26

Strongly reducing magnesium(0) complexes - Rösch, Bastian; Gentner, Thomas; Eyselein, Jonathan; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Nature, 2021)
A complex of a metal in its zero oxidation state can be considered a stabilized, but highly reactive, form of a single metal atom. Such complexes are common for the more noble transition metals. Although rare examples are known for electronegative late-main-group p-block metals or semimetals1-6, it is a challenge to isolate early-main-group s-block metals in their zero oxidation state7-11. This is directly related to their very low electronegativity and strong tendency to oxidize. Here we present examples of zero-oxidation-state magnesium (that is, magnesium(0)) complexes that are stabilized by superbulky, monoanionic, β-diketiminate ligands. Whereas the reactivity of an organomagnesium compound is typically defined by the nucleophilicity of its organic groups and the electrophilicity of Mg2+ cations, the Mg0 complexes reported here feature electron-rich Mg centres that are nucleophilic and strongly reducing. The latter property is exemplified by the ability to reduce Na+ to Na0. We also present a complex with a linear Mg3 core that formally could be described as a MgI-Mg0-MgI unit. Such multinuclear mixed-valence Mgn clusters are discussed as fleeting intermediates during the early stages of Grignard reagent formation. Their remarkably strong reducing power implies a rich reactivity and application as specialized reducing agents.
CRIS-Team Scopus Importer:2021-05-14